Analysis of Iranian Breast Cancer Research: A Scientometric Study - Ali Akbar Khasseh; Sholeh Zakiani; Faramarz Soheili (Tehran University of Medical Sciences, 2018)
Background and Aim: Scientometric studies are one of the most effective methods of scientific evaluation in databases. The aim of this study was to investigate Breast cancer in Iran from 2000-2016. Materials and Methods: This study has an applied approach and was conducted using scientometric indices. The st tistical population was the indexed articles related to Breast cancer between the years 2000 and 2016 by Iranian researchers at the Science Web site. Results: During the period 2000-2016, researchers have published 2198 articles on Breast cancer that indicate a steady and steady increase in the number of studies conducted in this area. The results of the study showed that Qaderi is the most prolific researcher in the field of Breast cancer in terms of the number of articles in Iran, Ebrahimi and Montazeri are in the second and third positions respectively. The highest H-index belongs to Montazeri, Qaderi and Abraham, respectively. Researchers in the field of Breast cancer have collaborated with researchers from 65 countries and more with the United States and Canada. The most co-operation has been between researchers in Tehran and Tabriz. The analysis of the keywords used in Breast cancer research in the form of supragloss showed that Iran, Apoptosis and Polymorphism were the most frequent keywords in the studied works. Conclusion: The upward trend in Breast cancer research indicates the growing importance of this area in Iran. Given the global growth of Breast cancer research and the importance of international research participation, Iranianresearchers should more and more engage in scientific collaboration with their counterparts abroad.